2019
DOI: 10.2196/12364
|View full text |Cite
|
Sign up to set email alerts
|

Features and Educational Content Related to Milk Production in Breastfeeding Apps: Content Analysis Informed by Social Cognitive Theory

Abstract: Background Low milk production is one of the main reasons for premature breastfeeding cessation. Smartphone apps have the potential to assist mothers with promoting, interpreting, tracking, or learning about milk production. It is not known whether breastfeeding apps contain high-quality, engaging, and diverse content and features that could be used by mothers to increase their breastfeeding self-efficacy and answer their questions about milk production. Objective The o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…A total of 40 iPhone and 42 Android apps were included in the final sample (N=82) of which 80 were free to users; only 2 paid iPhone apps remained in the final sample (Figure 1). The final sample is comparable to those of previous infant-feeding app studies, which included 41 to 77 apps [18,20,21].…”
Section: Samplementioning
confidence: 71%
See 1 more Smart Citation
“…A total of 40 iPhone and 42 Android apps were included in the final sample (N=82) of which 80 were free to users; only 2 paid iPhone apps remained in the final sample (Figure 1). The final sample is comparable to those of previous infant-feeding app studies, which included 41 to 77 apps [18,20,21].…”
Section: Samplementioning
confidence: 71%
“…The schema contained 87 distinct app characteristics and features. We defined features according to Sidhu et al [21] as any "opportunity for user interaction with the app (e.g., a button)." Descriptive characteristics were derived from the app's download page and included the name of the app, website link, download date, version number, date of last update, developer or seller name and affiliation (ie, commercial, government, nongovernment organization, university, unknown, or other), whether and which experts or end users were involved in the app development process, user rating (ie, number of stars out of 5), number of user reviews, app category (ie, medical, lifestyle, health and fitness, parenting, or other), language options, cost of basic and premium app versions, and age rating (not unlike a movie rating, each platform recommends the minimum maturity level of app content for end users by age, ie, >0, >4, >12, or >17).…”
Section: Measurementmentioning
confidence: 99%
“…The importance of educational tools based on self-efficacy is recognized in the literature and research has shown that the use of these tools can facilitate learning and improve individuals' self-confidence (17,(20)(21) .…”
Section: Discussionmentioning
confidence: 99%
“…Self‐efficacy can interfere with actions and the adhesion of healthy behaviors, impacting the individuals' motivation and directly reflecting on their efforts to achieve a certain objective (O'Halloran et al., 2016). Thus, it is necessary to encourage professionals to develop and apply technologies that promote self‐efficacy, given its impact on health promotion, health education, and social support (Sidhu et al., 2019; You et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison between countryside and metropolis according to the intervention in the first moment (M0) and in the second moment (M2). Statistical test: Mann-Whitney U test professionals to develop and apply technologies that promote selfefficacy, given its impact on health promotion, health education, and social support (Sidhu et al, 2019;You et al, 2020).…”
Section: F I G U R Ementioning
confidence: 99%